Development of a videogame that introduces Don Quixote de la Mancha in its narrative - Torres-Sierra, Diego Alejandro (2024)
It is undeniable that literature has been one of the most important artistic expressions, having great cultural relevance and social impact, but nevertheless it does not reach all audiences largely due to lack of interest, then it seeks to promote and / or encourage literature and what better reference than Don Quixote de la Mancha by Miguel de Cervantes Saavedra. For this, the narrative of the book will be introduced in a medium with more reach and impact on young people, such as video games, which have great attention and disposition of the young public, in video games you have to know how to read to achieve an adequate machine-player interaction, but not only reading is enough since in many video games to reach an understanding of the topics presented and / or advance in the progress of the same, a certain abstraction is needed, having that same ability in literature. Exercising in the user thoughts and / or reflections that allow an advance and understanding of the issues and not just a mechanical exercise. The relationship between literature and video games is in the ability of both to tell and transmit stories with a real impact, with the aim of adapting stories from books into video games not only to demonstrate the impact of video games but also to expose the stories of literature also giving an incentive to the world of literature. Thus having this relationship a purpose beyond that of entertainment, being an educational and learning purpose.